Reporting Quality of the Abstracts for Randomized Controlled Trials in Pediatric Dentistry - Gopinath, Vellore Kannan; Shetty, Raghavendra M.; Renugalakshmi, Apathsakayan; Dharmarajan, Lalli; Prakash, Ponnudurai Samuel Gnana; Jayaraman, Jayakumar (European Journal of Dentistry, 2023)
Objectives The purpose of this study is to systematically appraise the reporting quality of abstracts for randomized controlled trials (RCT) published in pediatric dentistry using Consolidated Standards of Reporting Trials (CONSORT) for abstracts and to analyze the relationship between the characteristics of the RCT to the quality of abstracts.Materials and Methods RCTs published in Pediatric Dentistry were retrieved from the PubMed database from 2016 to 2021. The quality of abstracts was appraised using CONSORT for abstracts checklist by two independent reviewers.Statistical Analysis In descriptive statistics, frequency and percentage analysis were used for categorical variables, whereas mean and standard deviation were used for continuous variables. To find the significant difference between the bivariate samples in independent groups, Mann–Whitney U test was employed. Multivariate analysis was performed using Kruskal–Wallis test and Mann–Whitney U tests. Probability value of p-value less than 0.05 was considered as statistically significant.Results Two hundred abstracts were included in the study. All the abstracts adequately reported the “objective” item, whereas only 2 and 4% of abstracts adequately addressed “randomization” and “harms” items, respectively. A significant relationship was observed between the continent of first author/corresponding author, number of authors, impact factor, adherence to CONSORT guidelines, word count, focus of study, and apriori protocol registration to the quality of abstracts (p < 0.05).Conclusion The abstracts of the RCT included in the study did not adequately follow the CONSORT for abstract guidelines. Adherence to the reporting guidelines would improve the overall reporting quality of abstracts of RCT published in Pediatric Dentistry. The overall mean score of the abstracts was 6.80 out of 15 indicating that the abstracts did not adequately follow the CONSORT for abstract reporting guidelines.
Keywords: abstract; Pediatric Dentistry; reporting quality; randomized controlled trials